Persepsi Masyarakat tentang Pinjaman Online : Studi Kasus Masyarakat Plaju Kota Palembang Sumatera Selatan - Fajrul Alfatih; Muqowim Muqowim; Baldi Anggara (ISLAMIKA, 2023)
The purpose of this study is to provide an overview of how people perceive online loans. The approach used is a qualitative approach. This type of research is a type of case study research. Sources of data in this study were generated from informants, namely the public, sources of relevant journal books that had previously existed articles and previous research. Data collection techniques were obtained by means of interviews and observations comparing with data in the same journals. While the data analysis technique in this study used interactive model analysis using three techniques, namely: data reduction, data display, and drawing conclusions. The results of this study show that people's perceptions of online loans are considered as a solution to the economic problems faced by the community, there are even some people who have made online loans an addiction to solve their economic problems, we cannot deny that online loans are very much needed in society, especially in the masses after this pandemic. While the impact of ilegal online loans is also very dangerous for users such as high interst rates, risk of leaked contacts, terror thereats, the risk of contacts being tapped, loss of privacy.